Dysphemism in the form of hatred and profanity towards forest destroyers in Indonesian poetry - Harun, Mohd.; Artika, Wiwit; Wildan, Wildan (Studies in English Language and Education, 2023)
Environmental challenges have inspired poets to use poetry as media to convey protest, sadness, or anger toward environmental damage. As a form of artistic expression, poetry is a powerful medium to convey concerns about ecology. This study aims to describe expressions of dysphemism in the form of hatred and profanity towards forest destroyers in Indonesian poetry. This qualitative study collected data from the three anthologies, namely (1) Riwayat Asap Membungkam Jerebu Lewat Sastra (The History of Smoke Silencing Haze through Literature), (2) Puisi Hijau Resonansi Serindit (Green Poetry: The Resonance of the Magpie Robin), and (3) Metamorfosis Rimba Sehimpun Puisi Hijau Warga SMA Cendana dan Penyair Tamu (Metamorphosis of the Jungle: A Collection of Green Poetry by Cendana High School Students and Guest Poets). The data were analyzed based on the theory of ecocriticism. The study shows that Indonesian poets (1) expressed hatred using the diction of greed combined with avarice expressions, and (2) expressed profanity using curse expressions. These dictions or expressions show that Indonesian poets are concerned about natures existence. If the situation is reversed, i.e., the forest and the earth are damaged, poets can act harshly according to the context and situation; they hate and condemn through their poetry. Through the use of dysphemism, environmental poetry encourages reflection and awareness of environmental damage caused by irresponsible human actions. The poem invites readers to consider the consequences of these actions and encourages changes in behavior to protect nature.